Analisis Maqashid Al-Khamsah Pada Produk Asuransi Syariah - Nadin; Solahuddin Al-Ayubi (Mumtaz Publishing, 2024)
This research aims to analyze Sharia maqashid in Sharia insurance products. The study of Sharia maqashid in Sharia insurance in this research is conducted with a philosophical approach, namely analyzing maqasid Sharia in insurance products descriptively and analytically. The results of this research indicate that the application of maqashid in Sharia insurance products covers five aspects known as al-kuliyyah al-khams, including protecting religion (hifz al-din), which is related to the perfection of human worship, such as pilgrimage insurance; protecting life (hifz an-nafs), such as prevention against threats to life and mental health; protecting intellect (hifz al-‘aql), such as ensuring future education; protecting lineage (hifz an-nasl), such as providing education funds aimed at the welfare of heirs; and preserving wealth (hifz al-maal), where Sharia insurance based on the tabarru contract for mutual assistance helps preserve the community's money in terms of its existence. This can be achieved by preserving what is acquired and achieved in the form of money and working for its growth and enhancement. Regarding its absence, this can be done by trying to avoid the loss of money obtained from it. Thus, Sharia insurance based on mutual assistance can help protect wealth from loss and manage wealth in accordance with Islamic principles. Keywords: Maqashid Syariah, Islamic Insurance, Maqasid al-Khamsah.